Αλληλογραφία με δικηγόρους.
Αλληλογραφία των Δημάρχων Κοζάνης με τους παρακάτω δικηγόρους: 1)Ιωάννη Τσιτσελίκη, 2)Λάζαρο Κίκα, 3)Ιωάννη Νάτσινα, 4)Ιωάννη Αντωνιάδη, 5)Άγγελο Μπακόπουλο, 6)Γεώργιο Βαρβούτη, 7)Ιωάννη Βίσκο, 8)Ιωάννη Γκόρα, 9)Δημήτρη Μανώλα, 10)Δημοσθένη Δόκο, 11)Πάνο Καραλίβανο,12)Γεώργιο Καράτζια,13)Ι.Καρότσης, 14)Νικόλαο Μανωλάκη, 15)Χρ.Οικονομόπουλο,16)Ι.Ρεπανά, 17)Χαρίση Τανή, 18)Κ.Τυφόξυλο, 19)Κ.Χατηκώστα και 20)Ι.Χρυσοχόου.